A new method of learning the function of the extraocular muscles. Issue 4 (27th January 2023) - Zhuang, Ruinan; Sun, Heng; Bian, Hui
Abstract: Understanding and memorizing the primary, secondary, and tertiary functions of the vertical recti and oblique extraocular muscles play a decisive role in correctly diagnosing various types of strabismus, determining the location of nervous system lesions, and formulating correct treatment plans. However, for beginners, rapid learning, memorization, and application of these extraocular muscle functions are challenging. To improve the teaching of strabismus in ophthalmology and help students overcome the core learning difficulties, our team developed a gesture method based on a functional diagram of the extraocular muscles and a corresponding rhyme to teach clinical medicine students. The effects of the gesture method were determined by using in‐class quizzes and self‐confidence levels. Students' evaluations of the gesture method were assessed using a questionnaire survey. The gesture method significantly improved the mean scores on the tests (4.85 ± 1.65 vs. 6.31 ± 1.87 vs. 6.80 ± 1.45, all p < 0.001) and self‐confidence scores (20.83 ± 4.06 vs. 27.38 ± 4.88 vs. 28.69 ± 3.53, all p < 0.001) of the students. The evaluations showed that the students were satisfied with the auxiliary memorization learning method. This new method could help students better understand and remember the function of the extraocular muscles, and is a valuable auxiliary teaching strategy.